Pengolahan Bahan Koleksi Anak di Taman Bacaan Forhati Medan - Yusniah Yusniah; Siti Masitoh; Nur Hayati Gultom; Eka Nursah Pitri; mam Hardani Ritonga (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
The Community Reading Center is a facility organized by the government and the community to provide information and reading opportunities, and is an ideal place for the community to play and learn to read. If you wish, the Forhati Reading Gardens collection can be borrowed, but there are conditions for borrowing books. The purpose of this research is to find out whether the Forhati Community Reading Center has experienced an increase. This is the goal, because the Forhati Medan Community Reading Center already has a very large number of books. This study uses qualitative research methods with primary data and interviews. The survey results show that Forhati Reading Center has a collection of Forhati City Reading Center, a large collection of picture books, textbooks, dictionaries, etc. for visitors and is doing well by providing a collection of available books. Keywords: Children's Reading Collection Material, Community Reading Gardens